Criminal Liability for Crimes Against Humanity as a Problem of International Law - Diallo, Boubacar Sidi Diallo (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2019)
The article sets out the nature, the history and the general structure of the crime against humanity and provides a comprehensive analytical commentary of the elements of such crimes as a problem of international law. The contextual element determines that crimes against humanity involve either large-scale violence in relation to the number of victims or its extension over a broad geographic area (widespread), or a methodical type of violence (systematic). This excludes random, accidental or isolated acts of violence. In addition, Article 7(2) (a) of the Rome Statute determines that crimes against humanity must be committed in furtherance of a State or organizational policy to commit an attack. The plan or policy does not need to be explicitly stipulated or formally adopted and can, therefore, be inferred from the totality of the circumstances. In contrast with genocide, crimes against humanity do not need to target a specific group. Instead, the victim of the attack can be any civilian population, regardless of its affiliation or identity.